Characteristics of biological preparations for apple protection from the main pests in the Western Forest-steppe of Ukraine - Gunchak, M.; Hawryluk, L.; Vlasova, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The modern bioinsecticides impact was researched on the main apple agrocenosis in Western Forest-steppe of Ukraine. It has been determined that the microbiological preparations efficiency against the apple aphid (Schizotetranychus pruni Oudms), against garden spider mite and against the godling moth (Laspeyresia pomonella L.). It has been established that the mixture of biological preparations Koloradocide, powder in norm 3 kg/ha, and Gaubsin, solution in norm 10 l/ha have shown the synergestic effect and high impact on phytophages.